Short-term memory and sentence comprehension in Catalan aphasia - Salmons, Io; Muntané-Sánchez, Helena; Gavarró, Anna (Frontiers in Psychology, 2022)
The main goal of the present study is to investigate visual and verbal short-term memory side to side with sentence comprehension in Catalan-speaking subjects with aphasia in comparison with subjects without brain damage. We aim to examine whether there are any significant correlations between their performance on short-term memory and comprehension tasks in order to evaluate the hypothesis that linguistic and memory deficits in aphasia are the result of a dysfunction of a common mechanism, usually short-term memory. Eigthy-four control subjects and twelve individuals suffering from different types of aphasia were assessed using the Catalan version of the Comprehensive Aphasia Test (CAT-CAT), which includes one recognition task and two digit and word span tests to evaluate visual and verbal short-term memory, respectively, as well as a sentence-to-picture comprehension task. The results showed that the performance of subjects with aphasia was significantly low on all tasks. Yet, the logistic regression analysis revealed that the magnitude of the differences between the control and experimental group varied across subtests, and that visual short-term memory was better preserved than verbal memory. The results also showed that there were no significant correlations between memory and language comprehension, which rules out the hypothesis that the deficits observed are due to a common underlying mechanism. Individual variation was also observed, specially on memory subtests, which suggest that memory impairments cannot explain the comprehension deficit in aphasia.